The effect of leg compression garments on the mechanical characteristics and performance of single-leg hopping in healthy male volunteers - Gupta, Amitabh (BMC Sports Sci Med Rehabil, 2015)
BACKGROUND: Compression garments (CG) are commonly used by athletes to improve motor performance and recovery during or following exercise. Numerous studies have investigated the effect of CG on physiological and physical parameters with variable results as to their efficacy. A possible effect of commercially available CG may be to induce a change in leg mechanical characteristics during repetitive tasks to fatigue. This investigation determined the effect of CG on performance and vertical stiffness during single-leg-hopping to exhaustion. METHODS: Thirty-eight healthy, male participants, mean (SD) 22.1 (2.8) years of age performed single-leg hopping at 2.2 Hz to volitional exhaustion with a CG, without CG and with a sham. Differences in total duration of hopping (1-way repeated ANOVA) and dependant variables for the start and end periods (2-way repeated ANOVA) including duration of flight (t(f)), loading (t(l)) and contact (t(c)) phases, vertical height displacement during flight (z(f)) and loading (z(l)) phases, normalised peak vertical ground reaction force (F(zN)) and normalised vertical stiffness (k(N)), were determined. Bonferroni correction was performed to reduce the risk of type 1 error. RESULTS: There was no significant difference (p = 0.73) in the total duration of hopping between conditions (CG (mean (SD)) 89.6 (36.3) s; without CG 88.5 (27.5) s; sham 91.3 (27.7) s). There were no significant differences between conditions for spatiotemporal or kinetic characteristics (p > 0.05). From the start to the end periods there was no significant difference in t(l) (p = 0.15), significant decrease in t(f) (p < 0.001), z(f) and z(l) (p < 0.001) and increase in t(c) (p < 0.001). There was also a significant increase in k(N) from start to end periods (p < 0.01) ranging from 9.6 to 14.2%. CONCLUSIONS: This study demonstrates that commercially available CG did not induce a change in spatiotemporal or vertical stiffness during a fatiguing task. The finding that vertical stiffness increased towards the end of the task, while hopping frequency and duration of loading were maintained, may indicate that there was an alteration to the motor control strategy as fatigue approached. TRIAL REGISTRATION: Current Controlled Trials ACTRN12615000240549. Registered 17 March 2015.